Increasing trend of antimicrobial resistance in Shigella associated with MSM transmission in Barcelona, 2020–21: outbreak of XRD Shigella sonnei and dissemination of ESBL-producing Shigella flexneri. (10th February 2023) - Moreno-Mingorance, Albert; Mir-Cros, Alba; Goterris, Lidia; Rodriguez-Garrido, Virginia; Sulleiro, Elena; Barberà, M Jesús; Alberny, Mireia; Hoyos-Mallecot, Yannick; Descalzo, Vicente; Bravo, Albert; Roca-Grande, Josep; Viñado, Belén; et al.
Abstract: Background: Several countries have recently reported the detection of ESBL-producing Shigella sonnei associated with transmission among MSM. In a previous study by our group, 2.8% of Shigella spp. obtained from MSM in Barcelona between 2015 and 2019 were ESBL producers. Objectives: To describe and characterize the emerging ESBL-producing Shigella spp. associated with sexual transmission among MSM detected from 2020 to 2021 in Barcelona, elucidating their connectivity with contemporaneous ESBL-producing Shigella spp. from other countries. Results: From 2020 to 2021, we identified that among MSM, 68% of S. sonnei were XDR harbouring bla CTX-M-27 and 14% of Shigella flexneri were MDR harbouring bla CTX-M-27 . WGS analysis showed that the ESBL-producing S. sonnei were part of a monophyletic cluster, which included isolates responsible for the prolonged outbreak occurring in the UK. Our data also reveal the first emergence and clonal dissemination of ESBL-producing and fluoroquinolone-resistant S. flexneri 2a among MSM. Conclusions: We report an increasing trend of antimicrobial resistance in Shigella spp. among MSM in Barcelona since 2021, mainly as a consequence of the dissemination of XDR ESBL-producing S. sonnei, previously reported in the UK. These results highlight the importance of international collaborative surveillance of MDR/XDR S. sonnei and S. flexneri for rapid identification of their emergence and the prevention of the transmission of these pathogens.